New Issues in the Management of MDR/XDR-TB - Vinall, Phil (MD Conference Express, 2012)
In 2008 Dr. Michael D. Iseman of National Jewish Health said, “In roughly 55 years we have squandered our precious legacy of chemotherapy for…tuberculosis [TB].” William R. Bishai, MD, PhD, Director of the The KwaZulu-Natal Research Institute for Tuberculosis and HIV, Durban, South Africa, echoed this idea, saying that “HIV and multidrug- resistant [MDR] strains of TB threaten to reverse a half century of partial control of TB.” He was referring to the TB and HIV coepidemics in sub-Saharan Africa.